Organ-, sex- and age-dependent patterns of endogenous L1 mRNA expression at a single locus resolution. Issue 10 (22nd May 2021) - Stow, Emily C; Kaul, Tiffany; deHaro, Dawn L; Dem, Madeleine R; Beletsky, Anna G; Morales, Maria E; Du, Qianhui; LaRosa, Alexis J; Yang, Hanlin; Smither, Emily; Baddoo, Melody; Ungerleider, Nathan; et al.
Abstract: Expression of L1 mRNA, the first step in the L1 copy-and-paste amplification cycle, is a prerequisite for L1-associated genomic instability. We used a reported stringent bioinformatics method to parse L1 mRNA transcripts and measure the level of L1 mRNA expressed in mouse and rat organs at a locus-specific resolution. This analysis determined that mRNA expression of L1 loci in rodents exhibits striking organ specificity with less than 0.8% of loci shared between organs of the same organism. This organ specificity in L1 mRNA expression is preserved in male and female mice and across age groups. We discovered notable differences in L1 mRNA expression between sexes with only 5% of expressed L1 loci shared between male and female mice. Moreover, we report that the levels of total L1 mRNA expression and the number and spectrum of expressed L1 loci fluctuate with age as independent variables, demonstrating different patterns in different organs and sexes. Overall, our comparisons between organs and sexes and across ages ranging from 2 to 22 months establish previously unforeseen dynamic changes in L1 mRNA expression in vivo . These findings establish the beginning of an atlas of endogenous L1 mRNA expression across a broad range of biological variables that will guide future studies.